THE IMPORTANCE OF FORENSIC ACCOUNTING EXPERTISE IN THE FAIR RESOLUTION OF ACCOUNTING DISPUTES - Darvishov Sarvarbek Rustamovich (Galaxy International Interdisciplinary Research Journal, 2024)
The article highlights the importance of forensic accounting expertise in ensuring the economic security of the country and its role in the fair resolution of economic disputes arising during investigations, investigations and trials. It also provides information on the reforms carried out in the development of forensic accounting expertise and institutions and organizations that carry out forensic accounting expertise.